Safety Integrity Level Assessment and Certification of Localization Train Network Control Management System - 赵强; 常振臣; 李砾工; 王金田 (机车电传动)
In this paper, on the basis of analyzing the core work for train network control system SIL certification, the key contents of SIL assessment activity process in TCMS development safety lifecycle were summarized, and a specific method for the SIL index assessment was brought up. In particular, a clear schematic description on determination and allocation process for the safety requirements and tolerable risk failure rate of TCMS was conducted. Meanwhile, a calculation method for failure in time (FIT) of safety function was also described in detail.